Study of thermionic RF-gun phase-space dynamics and slice emittance under influence of external electromagnetic fields - K. Kusoljariyakul (2018)
A high brightness electron source of ultra-small emittance and high-average current is one of the most important components for future accelerators. In a RF-electron-gun, rapid acceleration can reduce emittance growth due to space charge effects. However, twisting or rotation of the transverse phase-space distribution as a function of time is observed in thermionic RF-electron-guns and may set a lower limit to the projected beam emittance. Such rotation being caused by the variation of the RF field with time may be compensated by fields from a specific cavity. In this work, we study RF-electron-gun phase-space dynamics and emittance under the influence of external fields to evaluate the compensation schemes. © 2010 Elsevier B.V. Allrights reserved.